Tradisi Rabu Wekasan dalam Persepsi Milenial: Studi pada Mahasiswa Fakultas Ilmu Sosial UNNES - Rikha Zulia; Azkia Shofani Aulia; Fafi Masiroh (LP2M UIN Sunan Kalijaga, 2022)
The Rabu Wekasan tradition deal with islamic values because it was made from the assimilation of Javanese and Islamic cultures. The implementation of The Rabu Wekasan tradition gives pro and contra from various circles, this condition impend continuity of the tradition. The cultural action need to be carried out through society participation, especially millennials as the next generation of this country have to save the Rabu Wekasan traditions and rituals. The information about millennial perceptions of The Rabu Wekasan tradition is very important to explore as a reference about the next actions of them in continuity of The Rabu Wekasan tradition. This study aims to tell the history of The Rabu Wekasan tradition and to analyze the perceptions of the Semarang State University Faculty of Social Sciences students as millenials about The Rabu Wekasan tradition. This research was conducted through observation, interviews, questionnaires and literature study. Sources of data collected are reduced, analyzed then concluded. The results show that The Rabu Wekasan tradition have a beginning from the worship of the Javanese people which then developed into a tradition. This is supported by it name which comes from the Javanese language. Millennial perceptions of The Rabu Wekasan tradition are positive, based on 100 students, 91% said that The Rabu Wekasan tradition is important to take care of, 82% felt responsible for take care of, 75% answered that the tradition is useful because it is a local identity and rich in meaning of life. [Tradisi Rabu Wekasan berkaitan erat dengan nilai-nilai Islam karena lahir dari asimilasi budaya Jawa dan Islam. Tradisi Rabu Wekasan dalam pelaksanaannya menuai pro dan kontra di berbagai kalangan, sehingga mengancam kelestarian tradisi tersebut. Gerakan kultural perlu dilakukan melalui andil masyarakat khususnya milenial sebagai penerus bangsa untuk menjaga tradisi dan ritualnya. Informasi terkait persepsi milenial terhadap Rabu Wekasan sangatlah penting untuk digali dalam rangka menjaga kelestarian tradisi tersebut, dan juga sebagai acuan untuk mengetahui tindakan milenial selanjutnya dalam melestarikan Rabu Wekasan. Penelitian ini bertujuan mengetahui sejarah Rabu Wekasan serta menganalisis persepsi mahasiswa Fakultas Ilmu Sosial (FIS) Universitas Negeri Semarang terhadap Rabu Wekasan. Penelitian dilakukan melalui observasi, wawancara, kuesioner dan studi pustaka. Sumber data yang terkumpul direduksi, dianalisis kemudian ditarik kesimpulan. Hasilnya didapatkan bahwa sejarah Rabu Wekasan berasal dari ibadah yang dilakukan masyarakat Jawa kemudian berkembang menjadi tradisi. Hal tersebut didukung dengan namannya yang berasal dari Bahasa Jawa. Persepsi milenial terhadap Rabu Wekasan merupakan persepsi positif, yang ditunjukkan dari 100 mahasiswa, 91% mengatakan bahwa Rabu Wekasan penting untuk dilestarikan, 82% merasa bertanggung jawab untuk melestarikan, 75% menjawab tradisi tersebut bermanfaat karena merupakan identitas lokal serta kaya akan pembelajaran dan makna hidup.]